Capturing Change: Comparing Pretest-Posttest and Retrospective Evaluation Methods - Jessica L. Gouldthorpe; Glenn D. Israel (EDIS)
Two models that are commonly used in Extension programming to capture change over a short period of time are the pretest-posttest model and the retrospective pretest (or post-then-pre) model. When deciding which model to use, Extension professionals should keep in mind that each participant has a knowledge base that includes both factual information and perceptions pertaining to factual information. As you read about the strengths and weaknesses of these two design models, consider how each model fits the evaluation situation to select the one that can best measure change in your program. This 4-page fact sheet was written by Jessica L. Gouldthorpe and Glenn D. Israel and published by the UF Department of Agricultural Education and Communication, January 2013.